Double pre-stenting for percutaneous pulmonary valve implantation - Felipe Hernández Hernández; Miguel Artaiz Urdaci; José Luis Zunzunegui Martínez (REC: Interventional Cardiology (English Ed.), 2022)
Pre-stenting of the right ventricular outflow tract (RVOT) is often performed before percutaneous pulmonary valve implantation to guarantee a stable landing zone. One common off-label indication is the presence of a large native RVOT, which requires the anchoring of an extra-large stent. This is the case of a 17-year-old woman with a repaired Fallot´s tetralogy admitted for the assessment of severe pulmonary regurgitation with RV dilatation (video 1 of the supplementary data). The patient was ranked as NYHA functional class III. The cardiac magnetic resonance imaging revealed the presence of a large RVOT with diameters of 27 mm x 26 mm (video 2 of the supplementary data). For SAPIEN XT valve implantation (Edwards Lifesciences, United States) and to prevent stent migration, the “double-stent” technique was used. A 57 mm AndraStent XXL stent (Andramed, Germany) was pre-mounted on a 26 mm balloon followed by distal-to-proximal implantation from right pulmonary artery to pulmonary trunk. Afterwards, a second 48 mm AndraStent XXL stent was pre-mounted on a 30 mm balloon and partially implanted overlapping the former stent (figure 1A). A stent that remained in the left pulmonary branch that...